(3cJGH JVef GdcdGe Ydi eSGFd eJaQbIs
(3ChdgG (B:s
(3jHOC HeSFdI GdeTi Edi GdML hMceg HGdfSHI Edi GdGTNGU hGdGMhGd s
(3BNQgG (B:s
(3hGdeQGO efce GdOYGA di HeKd gPG hcPdc cd ef fXQ ajg ef GUMGHfG heY gPG adGMhd hdG bhI EdG HGddg GdYdi GdYXje gh MSHfG hfYe Gdhcjd hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd s
Keywords: (3Gdabg GdESdGejs